Lifestyle-Induced Microbial Gradients: An Indian Perspective - Singh, Rashmi; Haque, Mohammed Monzoorul; Mande, Sharmila S. (Frontiers in Microbiology, 2019)
Introduction: Urbanisation is a globally pervasive trend. Although urban settings provide better access to infrastructure and opportunities, urban life-styles pose certain negative consequences on human health. A number of recent studies have found interesting associations between the structure of human gut microbiome and prevalence of metabolic conditions characterising urban populations. The present study attempts to expand the footprint of these investigations to an Indian context. Specific objectives include elucidating signatures and specific patterns/ gradients that characterise gut microbial communities based on resident habitat/ life-style (i.e. tribal and urban). Methods: Available 16S rRNA gut microbiome sequence datasets corresponding to urban and tribal populations from multiple regions of India have been rigorously compared to understand the overall community structure, resident taxonomic components, their correlations, (inferred) functional aspects, and available meta-information. Results: Gut microbiomes of urban and tribal communities are observed to harbour characteristically different diversity, taxonomic, and functional signatures. Prevotella, previously reported to be the dominant genus resident in Indian gut microbiomes, is found to have distinct OTUs and strains-specific oligotypes characterising resident habitats and diet-patterns. Analysis of encoded functions indicated relative higher preponderance of Propanoate metabolism (a beneficial function) in tribal cohort. In contrast, lipopolysaccharide biosynthesis pathway, associated with several metabolic disorders, is relatively enriched in gut microbiomes of urban dwellers. Overall, urban lifestyle and diet appear to impact the structure and function of gut microbiomes and results of this study provide further evidences of this detrimental association. Conclusion: This study attempts to study, in an Indian context, the impact of urbanisation on the human gut microbiome. The analysis elucidates interesting taxonomic and functional signatures characterizing the evolutionary transition in gut microbiomes (from tribal to urban). Insights obtained in this study are expected to improve upon our understanding related to community/ habitat specific diseases and metabolic disorders, disease susceptibility. The results, at a high-level, find applicability in providing context for researchers developing novel diagnostic or pre-disposition indicators as well as intervention targets and design of appropriate therapeutic regimes.